Sistem Pendukung Keputusan Seleksi Calon PASKIBRAKA 2023 Kota Medan Menerapkan Metode MAUT - Nisa, Khairatul (STMIK Budi Darma, 2024)
Paskibraka Selection is an activity carried out by DISPORA Medan City. Every year, the aim is to find the best sons and daughters who will be assigned as heirloom flag raisers at the State Palace during the Republic of Indonesia's Independence Day celebrations. At the end of the selection of Paskibraka candidates for Medan City, there were still many shortcomings. The Medan City Paskibraka Committee still uses manual methods to determine the final score for each participant from all stages of the test held. The assessment of the test stages with a relatively large number of participants will make it difficult for the committee to consider the assessment that has been determined appropriately and accurately. Based on the problems described above, a Decision Support System (DSS) is needed to overcome existing problems. By applying the Multi Attribute Utility Theory (MAUT) method which can provide decision making based on direct comparisons of various values accurately and quickly. It is hoped that it can help the Medan City DISPORA Committee in making decisions on accepting the selection of Medan City Paskibraka candidates. The results of this research show that the Decision Support System (SPK) built using the MAUT method can assess the selection of Medan City Paskibraka candidates with the results obtained 10 of the best alternatives, namely, A5 (Raga Rindang Harahap) with the highest final score of 0 006572 Boby Kurniawan Lubis) 0.003267, A9 (Vivi Novita Hasibuan) 0.003267, A16 (Ahmad Fikri) 0.003267, and A17 (Risma Yanti Patricia) 0.003267.